Copyright reconstructed rethinking copyright's economic rights in a time of highly dynamic technological and economic change - Hugenholtz, P. B. (Kluwer Law International, 2018)
"This book is the result of a collaborative academic research project ('Reconstructing Rights') that ran from the autumn of 2014 to the summer of 2017. The aim of the project was to 'reconstruct' the economic rights protected under EU copyright law, by bringing these rights more in line with economic and technological realities"--Preface